Drowning in emails: investigating email classes and work stressors as antecedents of high email load and implications for well-being - Kern, Marcel; Ohly, Sandra; Ďuranová, Lenka; Friedrichs, Juliane (Frontiers in Psychology, 2024)
Introduction: High email load has been associated with impaired well-being because emails impose specific demands, disturb the workflow, and thereby overtax individuals' action regulation towards prioritized goals. However, the causes and well-being-related consequences of email load are not yet well understood, as previous studies have neglected the interaction type and function of emails as well as co-occurring stressors as antecedents of high email load and have relied predominantly on cross-sectional designs. Methods: In two studies, we aimed to clarify the nature of email load through the lens of action regulation theory. The first study, a two-wave investigation with a fortnightly interval, examined the lagged relationships among email load, work stressors, strain, and affective well-being were analyzed. The sample included 444 individuals across various occupations and organizations, with 196 of them working from home or remotely at least part of the time. In the second cross-sectional study, we surveyed 257 individuals using a convenience sampling approach, 108 of whom worked from home or remotely at least partially. This study focused on evaluating how different email classes-distinguished by email interaction type (received vs. processed) and email function (communication vs. task)-serve as predictors of high email load.In Study 1, we found a positive lagged effect of high email load on strain, even when controlling for the co-occurring stressors time pressure and work interruptions. In addition, lagged effects of email load on time pressure and interruptions were identified, while no evidence was found for the reverse direction. The results of Study 2 suggest that only the number of communicationrelated emails received, but not the number of task-related emails received, or the number of all emails processed contribute to high email load. Conclusion: Findings suggest that email load can be considered a unique stressor and that different classes of email need to be distinguished to understand its nature. Clarifying the sources of email load can help develop effective strategies to address it.